Los recursos audiovisuales digitales utilizados por los profesores en la educación secundaria - Orlando González-Gómez; María Esperanza Rodríguez-Suárez; Rosy Reyes-Pinilla (Mundo Fesc)
With ICTs within reach of humanity and following a global pandemic, education has undergone a significant transformation, leading teachers to seek more technological environments for teaching, with audiovisual communication being one of the most sought-after media for this purpose. This article aims to understand the use of audiovisual resources by secondary school teachers at the Manuel Antonio Rueda Jara School in Villa del Rosario, Norte de Santander, Colombia. A quantitative methodology was used through a survey conducted in 2022 through the Google Forms platform. The results obtained indicate that teachers are receptive and interested in introducing the use of videos and other digital audiovisual resources in the classroom, although in practice they are using very few such tools. The study underscores the need to provide support and training to educators so they can efficiently use technology in the classroom, which will allow them to significantly renew their instructional methods. The successful integration of audiovisual resources not only ensures greater student motivation and engagement, but also opens up new opportunities for training and adaptation to different learning styles. Ultimately, this study highlights the importance of promoting the use of technology in education. Although a digital divide still exists, it is necessary to implement changes in knowledge acquisition in order to achieve significant innovation in teaching.